MAPPING THE TOURISM POTENTIAL OF SIDAN DAM IN ORDER TO SUPPORT THE DEVELOPMENT OF NEW RENEWABLE ENERGY AS AN ATTRACTION FOR GREEN TOURISM THROUGH EDUCOTOURISM IN BALI - Ni Nyoman Sri Wisudawati,; Anak Agung Istri Agung Maheswari,; Putu Dyah Permatha Korry,; I Ketut Nuraga, (International Journal of Social Science, 2024)
This research aims to map potential and formulate appropriate development strategies in the development of Sidan Dam as a green tourism-based destination that provides education and conservation of the surrounding nature. This research uses a descriptive qualitative approach through the analysis of natural, artificial, and cultural potentials that can support economic, socio-cultural aspects and reduce the impact on the surrounding environment. Data collection was conducted through field surveys, Focus Group Discussions (FGD), and documentation studies. Sidan Dam has significant potential to be developed as an ecotourism destination that integrates environmental conservation activities and education in tourism. The concept is relevant considering the adequate natural potential and the development of supporting facilities. The development of tourism at the Sidan Dam needs to focus on educational tourism infrastructure that is still under construction, which can support learning about water resource management and the surrounding environment, as well as the development of nature-based tourism activities that are conservation-oriented and do not harm the environment. The development of tourism in the Sidan Dam area is expected to provide sustainable benefits for the surrounding community and environmental preservation.